2018
DOI: 10.2991/itmr.2018.7.2.1
|View full text |Cite
|
Sign up to set email alerts
|

mHealth in Bangladesh: Current Status and Future Development

Abstract: Digital health has significant potential in health and health system potential. mHealth is one of the digital solutions, has been one of the focus in Bangladesh for the last couple of years. There is enormous potential in using mHealth within the healthcare sector to ensure healthcare quality, accessibility and affordability in developing countries including Bangladesh. A large number of people in developing countries, particularly in rural and remote areas, remained with no or little access to health care fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Our findings suggest that mConsulting is a viable option for remote and spatially marginalised communities with minimal access to healthcare services in LMIC settings. In the five countries studied, regulatory frameworks are in place through national ICT and e/mHealth policies [46][47][48][49][50][51][52][53][54][55]58,63 and mConsulting is already happening: nationally, services delivered through provider platforms are available and at the community level, a few healthcare workers and community members reported direct experience of locally conducted mConsulting (with healthcare workers using their own phones)in emergencies, for advice and for care follow-up. Most stakeholders expressed enthusiasm for mConsulting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that mConsulting is a viable option for remote and spatially marginalised communities with minimal access to healthcare services in LMIC settings. In the five countries studied, regulatory frameworks are in place through national ICT and e/mHealth policies [46][47][48][49][50][51][52][53][54][55]58,63 and mConsulting is already happening: nationally, services delivered through provider platforms are available and at the community level, a few healthcare workers and community members reported direct experience of locally conducted mConsulting (with healthcare workers using their own phones)in emergencies, for advice and for care follow-up. Most stakeholders expressed enthusiasm for mConsulting.…”
Section: Discussionmentioning
confidence: 99%
“…34 In urban Tanzania, 82% men and 62% women own mobile phones compared to 74% men and 40% women in rural areas. 35 In all five countries, technology-enabled healthcare delivery is embedded in national policies, including on information and communication technology (ICT) (Nigeria 52 ) and digital futures (Pakistan, 46 Tanzania 49,58 and Bangladesh 54,63 ). Specific electronic/eHealth and mobile/mHealth policies are in place in Tanzania, 47 Kenya 50,51 and Bangladesh 53 (Table 1).…”
Section: Study Setting: Country-contextmentioning
confidence: 99%
“…However, a substantial number of research about mHealth services has been found in different context of Bangladesh, i.e. mHealth apps in Bangladesh (Karim et al, 2016), readiness of the community for mHealth in rural context (Khatun et al, 2015), perceived services quality dynamics (Akter et al, 2010b), trustworthiness in mHealth services (Akter et al, 2011), telemedicine adoption in rural areas (Rahman and Hoque, 2018), mHealth and eHealth initiatives in Bangladesh (Ahmed et al, 2014), adoption of portable health clinics in rural areas (Hossain et al, 2019), assessing the mHealth success in Bangladesh (Hossain, 2016), adoption intention of mHealth from demand side perspective (Shareef et al, 2014), health information seeking behavior (Andaleeb, 2008), mHealth status and challenges in Bangladesh (Alam, 2018), mHealth adoption by the elderly users (Quaosar et al, 2018), mHealth adoption behavior among the patients (Alam et al, 2020) etc.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that mConsulting is a viable option for remote and spatially-marginalised communities with minimal access to healthcare services in LMIC settings. In the five countries studied, regulatory frameworks are in place through national ICT and e/mHealth policies 36,[46][47][48][49][50][51][52][53][54][55]78 and mConsulting is already happening: nationally, services delivered through provider platforms are available and at community-level, a few healthcare workers and community members reported direct experience of locally-conducted mConsulting (with healthcare workers using their own phones) -in emergencies, for advice and for care follow-up. Most stakeholders expressed enthusiasm for mConsulting.…”
Section: Discussionmentioning
confidence: 99%
“…In all five countries, technology-enabled healthcare delivery is embedded in national policies, including on Information and Communication Technology (ICT) (Nigeria 46 ) and digital futures (Pakistan 47 , Tanzania 36,48 Bangladesh 49,50 ). Specific electronic/eHealth and mobile/mHealth policies are in place in Tanzania 51 , Kenya 52, 53 and Bangladesh 54 (Table 1).…”
Section: Methodsmentioning
confidence: 99%